Evaluasi Kerusakan Jalan dan Drainase Jalan (Studi Kasus : Ruas Jalan Sorogo – Gajahmada – Hayamwuruk, Kecamatan Cepu, Kabupaten Blora) - Ristiyanto, Hartono Guntur (SIMETRIS, 2024)
One of the causes of road damage is the presence of excess water due to inadequate drainage systems. Initial information related to the condition of existing drainage and also the damage to existing roads and the relationship between the two is needed for maintenance, evaluation, planning, and construction of both infrastructures so that the priority scale of handling can be applied for budget efficiency and effectiveness. Based on the problems above, this study was conducted with the aim of evaluating the condition of the road and its drainage. Data collection was carried out using survey and field observation methods. Analysis of pavement conditions using the Pavement Condition Index (PCI) method. Analysis of drainage conditions using a qualitative descriptive method with drainage performance benchmarks based on the Bina Marga Road Surface Drainage Design Guidelines (1990). The road sections that were the objects of the study were: Jalan Sorogo, Jalan Gajahmada, and Jalan Hayamwuruk in Cepu District. The characteristics of the road surface drainage surveyed were: road transverse slope, side channel dimensions, and channel sedimentation. The results of the analysis showed that the average road condition at the time of the study had a moderate level of damage with a PCI value of 46 while the drainage had a moderate level of damage both functionally and structurally. The drainage conditions that most affect the road are channel dimensions that are not in accordance with standards and changes in function from open to closed channels. While the most dominant effects of surface drainage conditions are: puddles and water infiltration. With the most dominant types of road damage due to puddles and infiltration are: crocodile skin cracks, peeling of the surface layer, and holes